A Full-Duplex, Dual-Polarization 10Gbps Radio over Fiber system with wavelength reuse for upstream signal - Masoud Deyranlou; Alireza Maleki Javan (AUT Journal of Electrical Engineering)
This study presents a full-duplex Radio-over-Fiber (RoF) system providing the users' wireless access with a bit rate of 10 Gbps over 40 GHz radio carrier. This system can be used in a centralized radio access network (C-RAN) architecture because we provide a fully analog front haul link between central station and base station. We can consider it as infrastructure between remote radio heads (RRHs) and baseband units (BBUs). The most appropriate choices in our case are using left and right-side bands of the DSB spectrum for both uplink and downlink streams and modulation of the data signal on both polarization of the optical carrier, as well as simplifying system structure, the bit rate of the proposed system, raised significantly. Furthermore, a method was provided to create redundancy for the optical fiber path and enhance system stability in case of a fiber cut. Optical external modulation is considered to be a good possibility to generate the optical mm-wave signal with high spectral purity. The transmission performance of the signal is analyzed in detail by analytical formulations and a full-duplex RoF link is built to verify our theoretical analysis results based on the simulation. Furthermore, the impacts of the fiber chromatic dispersion have been compensated in the RoF system with the dual-polarization carrier signal.